COENZYME Q10 IN PEDIATRICS - I.M. Osmanov; V.S. Sukhorukov; E.I. Kalambet ("Paediatrician" Publishers LLC, 2011)
The article presents the description of children's diseases related to primary and secondary disorders of cell energy exchange. Mechanisms of energotropic and antioxidant effect of ubiquinone (coenzyme Q10) in treatment of different diseases including those accompanied with deficiency of energy are described. Key words: children, ubiquinone, antioxidants, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (2): 146-149)